A detailed theoretical and experimental study on the NH, PO and CO stretching frequencies in two new phosphoric triamides and a statistical comparison with analogous structures. (15th January 2019) - Tarahhomi, Atekeh; van der Lee, Arie; Ośmiałowski, Borys
Graphical abstract: Two new C(O)NHP(O)-based phosphoric triamides were experimentally and computationally studied to evaluate the effect of the strength of the different NH…O(P/C) hydrogen bonds (HBs) on the NH/PO/CO stretching frequencies. These results were combined with a CSD and IR analysis of known phosphoric triamides. Abstract: Synthesis, X-ray structural, IR and NMR spectroscopic characterization of two new C(O)NHP(O)-based phosphoric triamides 2, 3, 6-F3 C6 H2 C(O)NHP(O)[ X ]2 ( X  = NC4 H8 O and NHC(CH3 )3 ) are presented. The NH…O(P/C) hydrogen bonds strengths and stretching frequencies shifts in hydrogen-bonded clusters forming graph-sets R 2 2 ( 8 ), R 2 2 ( 12 ) / R 2 2 ( 8 ) and R 2 2 ( 10 ) / R 2 1 6 in the two new structures and the previously reported structure of 2-FC6 H4 C(O)NHP(O)[NHCH(CH3 )2 ]2 are computationally evaluated using the Density Functional Theory (DFT) and the Atoms In Molecules (AIM) theory. It is in particular shown how the strengths of the different NH…O(P/C) HBs affect the frequencies shifts in hydrogen-bonded clusters. The study is completed by a statistical analysis using data from the Cambridge Structural Database (CSD) and the references that confirm the detailed experimental and theoretical investigations on the two new phosphoric triamides and the analogous compounds.